ANALISIS KINERJA BIAYA DAN WAKTU PROYEK PEMBANGUNAN SALURAN KANTOR PEMDA – EXIT TOL KEBOMAS GRESIK DENGAN MENGGUNAKAN METODE EARNED VALUE - Gupita, Princes Annastacia Ocha; Firdaus, Andrian Yusuf (Civil Engineering Study Program Faculty of Engineering, University of Palembang, 2023)
One of the supplementary structures rod ways that statisfies a technical need for road infrastructure is the drainage channel. The construction of the canal in this project was carried out from 01 July 2020 to 12 December 2020. With a contract value of Rp.4,339,944,950.06 and was carried out by the Contractor CV.Batu Mas. This project shows quite high progress, reaching 40.73% of project construction realization in the 11th week, while the planned progress of the project only reached 19.15% in that week. But time and money management are necessarry for the implementation circumstances in any project. Before using this control measure, the project’s performance must be known.The Earned Value method is one way to find out the Project Result Value. Combining schedule, cost, and job performance is the way to do this method.The performance in the project is influenced by several things. One of these things is used by means of a SWOT analysis. SWOT analysis is useful for knowing what variables affect project performance.